Lipofibromatous Hamartoma of the Palmar Cutaneous Branch of the Median Nerve - Hoellwarth, Jason S.; Goitz, Robert J. (Journal of Hand and Microsurgery, 2018)
Background Lipofibromatous hamartoma (LFH) is a benign tumor of peripheral nerves, most commonly reported in the median nerve, and often associated with carpal tunnel symptoms. There have been nearly 200 reported cases of LFH in the median nerve, but to the authors’ knowledge, this 10-year-old girl represents the first case report involving the palmar cutaneous branch.Methods An excisional biopsy of the mass was performed via a standard midline palmar incision. The tumor was found encapsulating the palmar cutaneous branch, and thus it was sacrificed.Results The incision healed without issue, but the patient reported numbness in the palm of her hand as was expected.Conclusion LFH is a benign tumor, although it can cause symptoms due to mass effect. If the diagnosis is uncertain or a patient is symptomatic, excisional biopsy can be performed even if involving a cutaneous nerve.
Keywords: lipofibromatous hamartoma; hamartoma; palmar cutaneous branch; median nerve; median nerve tumor